Extracurricular Activities Management at State Senior High School 1 Limbangan - Ghani, Argiansyah Amin; Yuliejantiningsih, Yovitha; Supriyono, Supriyono (Dinasti Publisher, 2026)
Argiansyah Amin Ghani. 2025. Extracurricular Management at SMA Negeri 1 Limbangan. Supervisors: (1) Dr. Yovitha Yuliejantiningsih, M.Pd (2) Dr. Supriyono Ps, M.Hum. The focus of this research is the relationship between planning, organizing, implementing, and monitoring and evaluating extracurricular activities at SMA Negeri 1 Limbangan. This research uses a qualitative approach described descriptively. The qualitative research contained in this thesis is a case study that produces in-depth information on an object. The research was conducted at SMA Negeri 1 Limbangan starting in August 2024. Data collection techniques in this study used interviews, observation, and documentation. This study found that extracurricular activities were designed by school management as a basis for implementing them from the beginning of the school year to the end of the semester. In carrying out these management activities, school policymakers conducted activity planning, organization, and quarterly program evaluations to ensure the effective implementation of all extracurricular programs at SMA Negeri 1 Limbangan. The conclusions from this activity were: Identity Media, Lobbying, Community Involvement, and Publication; organizing lobbying; community involvement; social investment; and publication. Implementation was carried out through intracurricular, co-curricular, and extracurricular activities; and monitoring was carried out through community involvement and lobbying. This study recommends strengthening management in implementing school work programs related to extracurricular activities at SMA Negeri 1 Limbangan.